Edukasi Ergonomi Saat Beraktivitas Fisik Sehari-Hari Pada Lansia Di Kelurahan Kramat Jati - Citra Puspa Juwita; Yolanda Firmawaty; Airene Gresya Pangaribuan; Abigail Angelina Wenur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2025)
The elderly are prone to musculoskeletal disorders due to non-ergonomic postures during daily activities. Ergonomic education is a preventive step to increase the awareness of the elderly in applying correct posture to reduce the risk of injury and improve quality of life. This community service activity aims to provide ergonomic education to the elderly in Kramat Jati Village to increase their understanding of correct posture during daily physical activities. This activity is carried out through several stages, namely training for cadres and the elderly, education about the importance of physical activity for the elderly, and ergonomic education in various daily activities. Education through presentation methods, demonstrations, and leaflets proved effective in increasing awareness and understanding in 50 participants. After providing education, all participants were able to answer questions correctly, which means that participants already know the right posture when doing daily activities. It is hoped that the application of ergonomic postures can help the elderly prevent musculoskeletal disorders and improve their quality of life.